Un palimpsesto urbano: de la Puerta del Sol al 15-M - Nancy Berthier; Marianne Bloch-Robin (Cahiers de Civilisation Espagnole Contemporaine)
This article begins by tracing the evolution of the imaginary of the Puerta del Sol in Madrid, which over time has become the theater of the representation of power and counter-power. In the twentieth century, the moving image has fixed the different stages of this power struggle. The movement of the «indignados» in 2011 is emblematic of this phenomenon inherited from the audiovisual traces that have constituted a palimpsest of the imaginary of the square, itself synecdoche of the city. Basilio Martín Patino’s documentary film, Libre te quiero, shot at the time of the occupation of the square in 2011, puts in scene the recovery of this symbolic space by a people in jubilation.